Uma proposta didática para o ensino da álgebra para um estudante com autismo - Agne, Sheila Mendes de Figueiredo (2025)
This Professional Doctorate thesis proposal in Science and Mathematics Education at the University of Passo Fundo is linked to the research line Theoretical and Methodological Foundations for Science and Mathematics Teaching. The aim was to create conditions for a student with autism to understand the concept of algebraic expressions and how to operate them, through an activity plan involving plane geometry and arithmetic using a geoboard, with the intention of fostering learning of this content. The guiding question of the research was: “What implications can an activity plan, designed for an autistic student and focused on algebraic expressions with the support of plane geometry and arithmetic, have on this student's learning of the content?” This research, configured as a case study and developed under a qualitative approach, is characterized as action research. Data collection was carried out through a field diary. The resulting educational product is an ordered sequence of activities guided by Lev Vygotsky’s Socio-Historical Theory and developed considering the stages of Didactic Engineering. The didactic sequence was designed for a 7th-grade student in elementary school, diagnosed with ASD Level 1, spanning twelve two-hour sessions, in a school located in São José do Ouro/RS. It was concluded that this research showed that gradual and mediated activities favored significant advances in the understanding and operation of algebraic concepts by a student with autism, highlighting the decisive role of intentional mediation and a supportive affective environment in the learning process. The instructional plan developed not only enabled the acquisition of the expected content but also contributed to the student’s overall development, reinforcing the importance of pedagogical interventions grounded in solid theoretical frameworks and accompanied by reflective analysis. Thus, this study offers a contribution to Inclusive Mathematics Education by pointing out a viable pedagogical path for teaching algebra to students with ASD, serving as a starting point for new research and practices aimed at a more equitable, just, and transformative education. The educational product accompanying this thesis is available at the following address on http://educapes.capes.gov.br/handle/capes/1174249.